The Validity of Unilateral Registration of Inheritance Land Transfer Rights - Amagadela, Gabriel (JURNAL AKTA, 2024)
This research analyzes the case in Supreme Court Decision Number 4041 K/PDT/2022, where the subject of the inheritance is a land right registered unilaterally by one of the heirs without the division of the inheritance among other heirs. The study discusses issues related to the system of registering the transfer of inheritance land rights and the validity of the certificate unilaterally registered without distribution to other heirs. The research methodology used is doctrinal. The findings indicate that when registering the transfer of inheritance land rights, it is mandatory to attach additional documents according to Article 111 of Regulation of the Ministry of Agrarian and Spatial Planning/National Land Agency Number 16 of 2021. Regarding the certificate unilaterally registered without distribution to other heirs, it is governed by Article 32 paragraph (2) of Government Regulation Number 24 of 1997, where the land certificate remains valid as proof of ownership as long as there is no objection or lawsuit filed within a period of 5 (five) years.